An imperialist competitive algorithm with feedback for energy-efficient flexible job shop scheduling with transportation and sequence-dependent setup times. (August 2021) - Li, Ming; Lei, Deming
Abstract: Flexible job shop scheduling problems have been extensively investigated in the past decade; however, transportation, sequence-dependent setup times (SDST) and energy efficiency are seldom incorporated together in flexible job shop. In this paper, energy-efficient flexible job shop scheduling problem (EFJSP) with transportation and SDST is considered and an imperialist competitive algorithm with feedback (FICA) is developed to minimize makespan, total tardiness and total energy consumption simultaneously. Assimilation and adaptive revolution are newly implemented by feedback and a new imperialist competition is presented by solution transferring among empires and the reinforced search. Extensive experiments are conducted and the computational results demonstrate that FICA provides promising results for EFJSP with transportation and SDST.